Estrategias de marketing para la comercialización de las artesanías textiles de la familia Anrango Panama del Cantón Otavalo, Provincia de Imbabura. - Gualsaquí Anrango, Jorge Luis (2015)
Otavalo owns a scenic charm, rich culture, history and business development. This Andean valley is home to the indigenous ethnic Kichwa Otavalo, famous for its textile and commercial skills, characteristics that have led to the largest indigenous market in South America or La Plaza de Ponchos Plaza Centenario, visited by people from around the world, allowing tourism development through their crafts that draw little attention from those interested in them. All this has allowed to prevail ethnic race that formed them and above all strive to keep both the city and abroad. Since Otavalo crafts have gained a good position internationally for its quality, designs and materials, especially those related to the textile craft, but few of them have become renowned. According to this it is that even craft workshops where textiles such crafts traditionally performed and that despite technological advances keep ancestral knowledge of peoples and that are necessary to keep alive in ways that contribute to the premises remain sumak kawsay established. The textile craft workshop Filia. Anrango Panama, located in the community of the Band is a family business that produces cotton cloth fabric colors and one color tone based on synthetic threads using the Spanish loom, which was used in colonial mills in past witnessed many indigenous craftsmen perish by exploitation, but thanks to his constant struggle for freedom, left a cultural legacy that aims to keep indigenous tradition alive. Completion of this work will allow the textile handicraft that is made in the workshop of Filia. Anrango Panama to position itself in the market, taking into consideration their traditional way of looking icrementar development gains, besides promoting tourism and handicrafts in Otavalo, revealing in this case the process of elaboration of textile crafts in the workshops of the family Anrango Panama which is very interersante for visitors, and thus make the traditional process can compete in local and international markets would be a vision of the future. What motivated to get more opportunities to improve the product and thus standardizing new models in line prodcutos establishing innovative besides having a reasonable price for loyal customers and clients in common.